Efficiency of the Multisource Information of the Biotronics Systems - Gužauskas, R.; Eidukas, D.; Balaišis, P. (Elektronika ir Elektrotechnika, 2010)
The conception of the information of biotronics systems (BTS) was formulated. The main BTS multi-source information groups were distinguished and their classification was presented. The BTS multi-source information usage scheme example was presented. Efficiency evaluation principles of local and external, single-parametric and multi-parametric, direct and indirect information were analyzed. The efficiency evaluation possibilities of the random multi-source BTS information were illustrated.